The effect of glycosylation on the stability of exogenous xylanase under in vitro proteolytic conditions similar to the rumen - Casey, N.H. (Norman Henry) (University of Pretoria, 2013)
Dissertation (MSc (Agric))--University of Pretoria, 2005.